Philosophical reflection on the application of generative artificial intelligence in education - Wei, Sun; Dolska, Olha (Національний технічний університет "Харківський політехнічний інститут", 2025)
The study finds that the application of generative AI in the field of education has triggered three major philosophical dilemmas: first, the ontological crisis, where GenAI has jumped from a tool to a "cognitive agent", reconstructing the essence of educational existence; second, the epistemological rupture, where the hegemony of algorithmic knowledge suppresses critical thinking; third, the ethical and political conflicts, where the digital divide exacerbates educational inequality. Based on this, the study proposes a human-centered governance framework: at the philosophical level, ensuring that AI serves the all-round development of human beings; at the practical level, constructing a national ethical review mechanism and a governance system for cultivating teachers' "technical humanistic" dual capabilities. The research confirms that only by taming instrumental rationality with value rationality can the dialectical transcendence of GenAI's educational application be realized.

Дослідження показує, що застосування генеративного штучного інтелекту в галузі освіти викликало три основні філософські дилеми: по-перше, онтологічну кризу, коли GenAI перетворився з інструменту на "когнітивний агент", реконструюючи сутність освітнього існування; по-друге, епістемологічний розрив, коли гегемонія алгоритмічних знань пригнічує критичне мислення; по-третє, етичні та політичні конфлікти, коли цифровий розрив посилює освітню нерівність. Виходячи з цього, дослідження пропонує систему управління, орієнтовану на людину: на філософському рівні – забезпечення того, щоб штучний інтелект служив всебічному розвитку людини; на практичному рівні – створення національного механізму етичного огляду та системи управління для розвитку «техніко-гуманістичних» подвійних здібностей вчителів. Дослідження підтверджує, що лише шляхом поєднання інструментальної раціональності з ціннісною раціональністю можна досягти діалектичної трансцендентності освітнього застосування GenAI.
Філософські роздуми про застосування генеративного штучного інтелекту в освіті
Keywords: generative AI; educational application; philosophical reflection; ethical dilemma; path reconstruction; генеративний ШІ; освітнє застосування; філософська рефлексія; етична дилема; реконструкція шляху